2013
DOI: 10.3341/kjo.2013.27.5.376
|View full text |Cite
|
Sign up to set email alerts
|

Acute Central Retinal Artery Occlusion Associated with Livedoid Vasculopathy: A Variant of Sneddon's Syndrome

Abstract: Livedoid vasculopathy (LV) is characterized by a long history of ulceration of the feet and legs and histopathology indicating a thrombotic process. We report a case of acute central retinal artery occlusion in a 32-year-old woman who had LV. She showed no discernible laboratory abnormalities such as antiphospholipid antibodies and no history of cerebrovascular accidents. Attempted intra-arterial thrombolysis showed no effect in restoring retinal arterial perfusion or vision. The central retinal artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Pieh and Safran (2003) consider that this "frequent, although rarely reported, morphologic feature" is characteristic of CRAO, a sentiment with which we concur. In many instances, however, the peripapillary axoplasmic ring goes unremarked upon (Song et al, 2013), or it is incorrectly attributed to anterior ischaemic optic neuropathy (AION) following combined CRA and PCA occlusion (Lee et al, 2002). In reality, no prelaminar accumulation of axoplasm occurs in eyes with simultaneous combined CRAO and PCA occlusion because infarction of RGC axon segments continues uninterrupted from the retinal NFL, through the ONH, and into the retrolaminar optic nerve (McLeod, 1976a;McLeod et al, 1980).…”
Section: Safronmentioning
confidence: 97%
“…Pieh and Safran (2003) consider that this "frequent, although rarely reported, morphologic feature" is characteristic of CRAO, a sentiment with which we concur. In many instances, however, the peripapillary axoplasmic ring goes unremarked upon (Song et al, 2013), or it is incorrectly attributed to anterior ischaemic optic neuropathy (AION) following combined CRA and PCA occlusion (Lee et al, 2002). In reality, no prelaminar accumulation of axoplasm occurs in eyes with simultaneous combined CRAO and PCA occlusion because infarction of RGC axon segments continues uninterrupted from the retinal NFL, through the ONH, and into the retrolaminar optic nerve (McLeod, 1976a;McLeod et al, 1980).…”
Section: Safronmentioning
confidence: 97%
“…Ophthalmologic complications include central retinal artery occlusion, central retinal vein occlusion, retinal neovascularization, homonymous visual field defects, and internuclear ophthalmoloplegia [ 37 - 42 ]. Rehany et al reported a young SS patient with internuclear ophtalmoplegia followed by ophthalmic artery occlusion [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic heparinMicrocatheter (Prowler 10, Codman Neuro) navigated through distal MMA and placed at meningo-ophthalmic arteryAngiogram showed improvement in angiographic visualisation of choroidal blush. FFA day 2 showed recanalizationNormal VA and VFsSong et al44, 2012HMNo definite thrombus or steno-occlusive lesion within OAUrokinase 500,000 unitsOA infused – details not given7 hrs later, no improvement in FFA.FFA 3 days post procedure showed near complete resolution of retinal arterial perfusion. Fundus photography showed severe retinal atrophy in macula and disc pallor.…”
Section: Resultsmentioning
confidence: 95%
“…Arteritic CRAO was excluded in 6 cases41,44,45,47,48 based on reported history (arteritic symptoms excluded) and investigations (normal CRP and ESR). Embolus composition was only mentioned in 1 case41 where Hollenhurst plaques were observed and this patient achieved VA of 20/20 after IAT.…”
Section: Resultsmentioning
confidence: 99%